JURNALISME LINGKUNGAN YANG SADAR LINGKUNGAN - Fajar, Arief (Universitas Muhammadiyah Surakarta, 2011)
In the principle, environmental journalism has same format to another journalism. However, the difference is a central issue in the news, coverage of environmental journalism focused on text production from the reality of environment such as the environmental damage caused of human error (pollution, flooding, landslides, and deforestation), local wisdom, conservation, waste, nature resource. According to categorization from Flournoy, environmental news consist of (Flournoy, 1989); Peristiwa yang ditampilkan dalam teks berita yang terkait dengan Bencana Alam, Perubahan Iklim, Global Warming, Penipisan Lapisan Ozon, dan lain-lainya seperti pengembangan teknologi serta kebijakan pemerintah terkait lingkungan. Most people know about environmental degradation such as deforestation, pollution industrial waste and the greenhouse effect through newspapers and television. But most environmentalists are not satisfied with the environmental news in newspapers and on television. They cite three mistakes that often appear in the news environment, such as: lack of information relevant to the background news, headlines are often misleading and lack of desire to think of risk coverage. (Abrar, 1993:59-60). The main discussion in this paper, invites critical discussion about the concept of environmental journalism.?